2007
DOI: 10.12968/jowc.2007.16.7.27062
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pH measurement as a method of wound assessment

Abstract: Wound pH measurements can be performed efficiently and are non-invasive, causing no discomfort to the patient. As the wounds healed, the pH reduced. This change in pH can help predict the likelihood of wound healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 13 publications
3
79
0
1
Order By: Relevance
“…Their review supports early determination of wound infection status by monitoring infection related wound fluid parameters [15]. Another study of acute and diabetic foot ulcers classified wounds as either unhealthy, granulating, or healing [16]. They observed that improving and healing wounds were associated with a lower pH (7.5-8).…”
Section: The Value Of Ph Level Of Chronic Woundsmentioning
confidence: 89%
See 1 more Smart Citation
“…Their review supports early determination of wound infection status by monitoring infection related wound fluid parameters [15]. Another study of acute and diabetic foot ulcers classified wounds as either unhealthy, granulating, or healing [16]. They observed that improving and healing wounds were associated with a lower pH (7.5-8).…”
Section: The Value Of Ph Level Of Chronic Woundsmentioning
confidence: 89%
“…They are also inactive in low pH (pH4) environments. These studies, among others suggest that lowering the pH of wound fluid might improve healing rates in non-healing wounds [16][17][18]. Modulating the pH level may also be one rapid, accurate, and sensitive method of controlling the infectious bioburden of a chronic wound [15].…”
Section: The Value Of Ph Level Of Chronic Woundsmentioning
confidence: 97%
“…Wounds presented with a pH of 8.5 or more, but as the wound began to heal pH values reduced to 8 and below. 31 Other studies have demonstrated a difference in pH of wounds classed as being in different stages of healing. Stage-3 ulcers had a pH of 7.6 compared with stage-1 ulcers with a more acidic and similar pH to intact skin (pH 5.4-5.6).…”
Section: The Ecmmentioning
confidence: 98%
“…[4] Many chemicals like acetic acid, hydrocolloids, occlusive carbon dioxide, honey and citric acid have been used for application to wounds as pH modifying agents. [5,6,7,8] Citric acid has been in use for a very long time, first in dental care and then subsequently in surgical dressings. [9,10] Use of citric acid is primarily based on pH modulation.…”
Section: Introductionmentioning
confidence: 99%